Game Design for Eysenck Method Personality Test Using Unity - Liniarto, Edbert; Nugroho, Erdhi Widyarto; Nugroho, Agus Cahyo (Soegijapranata Catholic University, 2024)
In this day and age, there continues to be a growth in technology that makes things easier and more effective. In addition, the distance that was originally a major problem for connecting, talking, exchanging thoughts or data with others disappeared because of the globalization that occurred. The growth of science and technology is basically a growth that aims to achieve and fulfill human aspirations and needs in using resources. Therefore, the idea arose to design a simple personality test game.The purpose of this research is to design a windows10 operating system-based game into the